Novel Nanoporous Carbon/Iron Oxide Catalyst for SO2 Degradation. (2019) - Stanisavljević, Maja; Janković, Savka; Milisavić, Dragana; Čađo, Marko; Kukrić, Zoran; Stević, Dragana; Kukobat, Radovan; Ilić, Predrag; Međed, Denis; Wojtan, Magdalena Parlinska; Atlagić, Suzana Gotovac
Abstract: A green chemistry approach for fabrication of active carbon, enriched with remediated iron is shown. Detailed characterization (HRSTEM, STM, and N2 adsorption) was performed, followed by active carbon soaking in iron and manganese ionic solutions obtained from remediated mining sludge. Novel forms of active carbons with round or needle-like oxide particles on the surface were obtained by combining these materials. The materials were tested as filters for sulfur dioxide, on sulfur-rich coals fume. After adsorption, the iron structures seem to play a stronger catalytic role in the filter regeneration, transforming the adsorbed sulfur dioxide into sulfuric acid.